Comparative Evaluation of Two Interface Tools in Performing Visual Analytics Tasks. - Jeong, Dong Hyun.; Greensmith, Tera Marie.; Ribarsky, William.; Chang, Remco. (Tufts University. Tisch Library., 2017)
In this paper, we performed a comparative evaluation to show the effectiveness of two interface tools, one a floating text-based menu (Floating-Menu) and the other a more interactive iconic tool (Interactive-Icon) We evaluated the use and human performance of both tools within one highly interactive visual analytics system. During task performance we tracked completion times, task errors, and captured coarsegrained interactive behaviors.